Cancer Surveillance in Healthy Carriers of Germline Pathogenic Variants in BRCA1/2: A Review of Secondary Prevention Guidelines. (20th June 2020) - Dullens, Boudewijn; de Putter, Robin; Lambertini, Matteo; Toss, Angela; Han, Sileny; Van Nieuwenhuysen, Els; Van Gorp, Toon; Vanderstichele, Adriaan; Van Ongeval, Chantal; Keupers, Machteld; Prevos, Renate; Celis, Valerie; et al.
Abstract : Germline pathogenic alterations in the breast cancer susceptibility genes 1 ( BRCA1 ) and 2 ( BRCA2 ) are the most prevalent causes of hereditary breast and ovarian cancer. The increasing trend in proportion of cancer patients undergoing genetic testing, followed by predictive testing in families of new index patients, results in a significant increase of healthy germline BRCA1/ 2 mutation carriers who are at increased risk for breast, ovarian, and other BRCA -related cancers. This review aims to give an overview of available screening guidelines for female and male carriers of pathogenic or likely pathogenic germline BRCA1/2 variants per cancer type, incorporating malignancies that are more or less recently well correlated with BRCA1/2 . We selected guidelines from national/international organizations and/or professional associations that were published or updated between January 1, 2015, and February 1, 2020. In total, 12 guidelines were included. This review reveals several significant discordances between the different guidelines. Optimal surveillance strategies depend on accurate age-specific cancer risk estimates, which are not reliably available for all BRCA -related cancers. Up-to-date national or international consensus guidelines are of utmost importance to harmonize counseling and proposed surveillance strategies for BRCA1/2 carriers.